The need to research refractory breathlessness. Issue 1 (January 2016) - Currow, David C.; Abernethy, Amy P.; Allcroft, Peter; Banzett, Robert B.; Bausewein, Claudia; Booth, Sara; Carrieri-Kohlman, Virginia; Davidson, Patricia; Disler, Rebecca; Donesky, DorAnne; Dudgeon, Deborah; Ekstrom, Magnus; et al.
The joint American Thoracic Society (ATS)/European Respiratory Society (ERS) statement "An official American Thoracic Society/European Respiratory Society statement: research questions in COPD" by Celli et al. [1] is a timely summary of the current evidence and the questions that arise directly from where that evidence reaches its limits. Such documents are crucial in framing research strategies for researchers and research funders. High-quality research is needed to improve quality of life for people with chronic refractory breathlessness in COPD http://ow.ly/Q2GDY